The Category Management Process and Responding to Customer Needs - Agnieszka Biernat-Jarka; Katarzyna Świerczyńska (Contemporary Economics)
This article presents the process of managing the product category of fast-moving (FMCG) in the example of tobacco products. Assumptions discussed the process developed by two companies working together. The presented results show that the process of category management is an extremely important activity in achieving the company sales and response for consumer needs. As a result of the implementation of category management process of tobacco products has been increasing the number of customers visiting outlets, increasing the number of marketed products, and ultimately increase the company’s profit.